Biomechanical changes from long‐term freezer storage and cellular reduction of tracheal scaffoldings. (5th August 2014) - Jones, Matthew C.; Rueggeberg, Frederick A.; Cunningham, Aaron J.; Faircloth, Hunter A.; Jana, Tanima; Mettenburg, Donald; Waller, Jennifer L.; Postma, Gregory N.; Weinberger, Paul M.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis To determine structural biomechanical changes in tracheal scaffolds resulting from cellular reduction and storage at −80oC. Study Design Laboratory‐based study. Methods Forty‐four rabbit tracheal segments were separated into four treatment groups: untreated (group A, control), cellular‐reduced (group B), storage at −80oC followed by cellular reduction (group C), and cellular‐reduced followed by storage at −80oC (group D). Tracheal segments were subjected to uniaxial tension (n = 21) or compression (n = 23) using a universal testing machine to determine sutured tensile yield load and radial compressive strengths at 50% lumen occlusion. Mean differences among groups for tension and compression were compared by analysis of variance with post‐hoc Tukey‐Kramer test. Results The untreated trachea (group A) demonstrated mean yield strength of 5.93 (± 1.65) N and compressive strength of 2.10 (± 0.51) N. Following treatment/storage, the tensile yield strength was not impaired (group B = 6.79 [± 1.58] N, C = 6.21 [± 1.40] N, D = 6.26 [± 1.18]; P > 0.10 each). Following cellular reduction, there was a significant reduction in compressive strength (group B = 0.44 N [± 0.13], P < 0.0001), but no further reduction due to storage (group C = 0.39 N [± 0.10]; P = 0.97 compared to group B). Conclusion The data suggest cellular reduction leads to loss of compressive strength. Freezing at −80°C (either before, or subsequent to cellular reduction) may be a viable storage method for tracheal grafts. Level of Evidence N/A. Laryngoscope, 125:E16–E22, 2015